Kajian Feminisme dan Citra Perempuan dalam Puisi Dongeng Marsinah Karya Sapardi Djoko Damono - Muhammad Aditya Wisnu Wardana (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2022)
As a response that interprets the author's sensitivity to various surrounding phenomena, literary works come with various theories and studies, one of which is the study of feminism and the image of women. The poem Dongeng Marsinah by Sapardi Djoko Damono is one of the literary works that comes with the study of feminism and the image of women to respond to the life of today's society. The data collection technique uses document analysis based on feminism literary theory. The interesting thing in the poem entitled Dongeng Marsinah by Sapardi Djoko Damono is the emergence of a women's movement against injustice or patriarchy through a literary work. The view of literary works in the poem entitled Dongeng Marsinah by Sapardi Djoko Damono has a reflection on today's social life. The images of women in the poem Dongeng Marsinah by Sapardi Djoko Damono include: (1) the image of a psychic woman; (2) the image of women in society; (3) the image of women in terms of behavior; and (4) the image of women from a physical point of view. The hope is that by understanding the meaning of the image of women in the poem, a woman should not be treated with violence physically, mentally, or sexually.